The Effect of Pomegranate Juice Supplementation on Muscle Damage, Oxidative Stress and Inflammation Induced by Exercise in Healthy Young Men - Ehsan Bayat-Chadegani; Hossein Fallahzadeh; Gholamreza Askari; Roza Rahavi; Zahra Maghsoudi; Azadeh Nadjarzadeh (مجله دانشکده پزشکی اصفهان, 2015)
Background: Epidemiological evidence has shown that antioxidant supplements may play an important role in preventing exercise-induced muscle damage and oxidative stress. Recent years, some researchers have shown high levels of unique compounds in pomegranate polyphenol antioxidants. The aim of this study was to evaluate the impact of natural pomegranate juice on oxidative stress, muscle damage and inflammation induced by exercise in healthy young men.